Putting food in the driver’s seat: aligning food-systems policy to advance sustainability, health, and security - Andrews, Elisabeth; Sanderson Bellamy, Angelina; , Food Policy Alliance Cymru; Bellamy, Angelina Sanderson; Buckland-Jones, Shea; Evans, Rhys; Lawrence, Ruth; Marsden, Terry; Mitchell, Gary; Palmer, Katie; Tomlinson, Holly; Tuddenham, Andrew; et al. (Frontiers in Sustainable Food Systems, 2023)
Food is a basic need, but seldom a basic policy area. Food systems are widely governed by disconnected policies distributed across a range of sectors including agriculture, education, health, environment, economy, and security. Failure to align food system strategies often results in these disparate policies operating at cross-purposes. Conventional food production and consumption practices contribute to biodiversity decline and climate change, cause diet-related health problems, are associated with worker exploitation, and create national security risks. Drawing on agroecology for cohesive national food strategies can provide benefits across all these sectors: supporting public health, environmental sustainability, economic stability, social cohesion, and national security and sovereignty.